Gut microbiota modulates depressive-like behaviors induced by chronic ethanol exposure through short-chain fatty acids - Hui Shen; Chaoxu Zhang; Qian Zhang; Qing Lv; Hao Liu; Huiya Yuan; Changliang Wang; Fanyue Meng; Yufu Guo; Jiaxin Pei; Chenyang Yu; Jinming Tie; et al. (Journal of Neuroinflammation)
Abstract Background Chronic ethanol exposure (CEE) is recognized as an important risk factor for depression, and the gut-brain axis has emerged as a key mechanism underlying chronic ethanol exposure-induced anxiety and depression-like behaviors. Short-chain fatty acids (SCFAs), which are the key metabolites generated by gut microbiota from insoluble dietary fiber, exert protective roles on the central nervous system, including the reduction of neuroinflammation. However, the link between gut microbial disturbances caused by chronic ethanol exposure, production of SCFAs, and anxiety and depression-like behaviors remains unclear. Methods Initially, a 90-day chronic ethanol exposure model was established, followed by fecal microbiota transplantation model, which was supplemented with SCFAs via gavage. Anxiety and depression-like behaviors were determined by open field test, forced swim test, and elevated plus-maze. Serum and intestinal SCFAs levels were quantified using GC-MS. Changes in related indicators, including the intestinal barrier, intestinal inflammation, neuroinflammation, neurotrophy, and nerve damage, were detected using Western blotting, immunofluorescence, and Nissl staining. Results Chronic ethanol exposure disrupted with gut microbial homeostasis, reduced the production of SCFAs, and led to anxiety and depression-like behaviors. Recipient mice transplanted with fecal microbiota that had been affected by chronic ethanol exposure exhibited impaired intestinal structure and function, low levels of SCFAs, intestinal inflammation, activation of neuroinflammation, a compromised blood-brain barrier, neurotrophic defects, alterations in the GABA system, anxiety and depression-like behaviors. Notably, the negative effects observed in these recipient mice were significantly alleviated through the supplementation of SCFAs. Conclusion SCFAs not only mitigate damage to intestinal structure and function but also alleviate various lesions in the central nervous system, such as neuroinflammation, and reduce anxiety and depression-like behaviors, which were triggered by transplantation with fecal microbiota that had been affected by chronic ethanol exposure, adding more support that SCFAs serve as a bridge between the gut and the brain.